Literature Review: Peran Strategis Pemimpin dalam Menciptakan Budaya Kerja yang Progresif dan Berkelanjutan - Abiyyu Mufadhdhal Zhafran Ammar; Avandi Akbar Basyarudin; Fitriyani Nurul Awaliyah; Wahyu Try Hartanto (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2025)
In the era of globalization and increasingly fierce business competition, companies need to have a progressive and sustainable work culture to stay relevant and grow. Leaders have a key role in shaping and directing organizational culture, which includes the values, attitudes, and behaviors desired in an organization. A progressive work culture can improve performance, innovation, and employee satisfaction and engagement. This study aims to understand the strategic role of leaders in creating a progressive and sustainable work culture in organizations. This research uses a literature review design with the SPIDER approach (Sample, Phenomenon of Interest, Design, Evaluation, and Research Type), this method was chosen because it is able to accommodate both qualitative and quantitative research. The results showed that leaders who have a clear vision, good communication skills, and active involvement in developing and maintaining organizational values, can create a progressive and sustainable work culture. Based on the discussion in this article, it can be concluded that leaders play a vital role in creating a progressive and sustainable work culture. With effective leadership, a work culture that supports sustainable development can be created, which in turn can improve organizational competitiveness and performance.